Potential Use of Rubber Powder as Cementitious Material - SHUKRI, NUR SYAZANA; ROSLAN, NURUL HIDAYAH (Progress in Engineering Application and Technology, 2025)
Tire production for vehicles is increasing exponentially given the rapidly growing population and transportation development. This study was conducted due to the lack of journals in determining the potential of rubber powder as a replacement material in mortar. The purpose of this study is to evaluate the potential use of rubber powder in mortar as a cementitious material and to determine the optimum amount of rubber powder to use as a cement replacement material in mortar. The testing that is used for knowing the potential of rubber powder was regarding the X-ray fluorescents test, moisture content, pozzolanic activity test, and strength activity index. A compressive strength test was used to determine the optimum amount to use as cement replacement. The data for the X-ray fluorescents test shows that rubber powder contains chemical elements in low amounts. The strength activity index data was 73% and 39% for 7 days and 28 days. This shows that the strength activity index for mortar with 20% rubber powder for both days does not exceed the minimum requirement of 75% as stated in ASTM C618. The pozzolanic activity test shows the rubber powder does not react with saturated lime solutions. Rubber powder was melted before reaching 105°. The compressive strength test shows that the optimum use of rubber powder in mortar mix at 5% to 10% because it is still in an acceptable range. This study should contribute to the next research on combining rubber powder with other addictive with high pozzolan.